2021
DOI: 10.3390/w13020178
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Islands Resilience to Extreme Events: Do Earthquake and Tsunami Play a Role?

Abstract: Barrier islands are indicators of coastal resilience. Previous studies have proven that barrier islands are surprisingly resilient to extreme storm events. At present, little is known about barrier systems’ resilience to seismic events triggering tsunamis, co-seismic subsidence, and liquefaction. The objective of this study is, therefore, to investigate the morphological resilience of the barrier islands in responding to those secondary effects of seismic activity of the Sumatra–Andaman subduction zone and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…They underwent substantial landward retrogradation and narrowing over the investigated period (Figure 7). This asymmetry is also observed offshore, in the bathymetry of the shoreface (Meilianda et al, 2021), with a steeper shoreface being observed west of the Aceh River, which may result from a more limited input of sediment in the west. Part of the asymmetry may also result from faster subsidence in the western part of the delta, which occupies a tectonic trough located over the trace of the Great Sumatra Fault.…”
Section: Cartographic Dataset Of Aceh: Advantages and Limitsmentioning
confidence: 70%
See 1 more Smart Citation
“…They underwent substantial landward retrogradation and narrowing over the investigated period (Figure 7). This asymmetry is also observed offshore, in the bathymetry of the shoreface (Meilianda et al, 2021), with a steeper shoreface being observed west of the Aceh River, which may result from a more limited input of sediment in the west. Part of the asymmetry may also result from faster subsidence in the western part of the delta, which occupies a tectonic trough located over the trace of the Great Sumatra Fault.…”
Section: Cartographic Dataset Of Aceh: Advantages and Limitsmentioning
confidence: 70%
“…Other strategies must therefore be adopted to investigate long‐term dynamics on these deltas. Historical maps, aerial photographs, and satellite images have been used to track the evolution of river channels (Gautier et al, 2007; Harmar & Clifford, 2006; Magliulo et al, 2016) and coastal landforms (Jana & Bhattacharya, 2013; Jonah et al, 2016; Kankara et al, 2015; Kumar et al, 2010; Meilianda et al, 2021; Stive et al, 2002) over decades to centuries. Geographic information systems (GISs) are commonly used to overlap digitized historical maps, aerial photographs, and satellite images (Bisson & Bini, 2012; Giacomelli et al, 2018) and create time‐series of landscape change.…”
Section: Introductionmentioning
confidence: 99%
“…The papers concerning the analysis of terrestrial and marine landforms in coastal and shallow water specifically deal with geomorphological mapping and landscape evolution [22,23], geoheritage and geodiversity [18,19], geohazards [16,20,21], and marine and landscape ecology [28].…”
Section: Topic 1: Terrestrial and Marine Landforms In Nearshore Areasmentioning
confidence: 99%
“…Meilianda et al [16] performed a spatial analysis on multisource datasets to investigate barrier islands' morphological changes along Sumatra Island coasts (Indonesia), as a result of the secondary effects of the seismic activity related to the Sumatra-Andaman subduction and the Great Sumatran Fault system. In particular, the authors documented that the 2004 megatsunami irreversibly changed barrier islands on the investigated stretches of the coast.…”
Section: Topic 1: Terrestrial and Marine Landforms In Nearshore Areasmentioning
confidence: 99%
See 1 more Smart Citation